Long-term mortality from birth in individuals with and without isolated congenital aortic stenosis: a nationwide, register-based cohort study. (3rd October 2022) - Magnusson, C; Mandalenakis, Z; Dellborg, M; Eriksson, P; Fedchenko, M; Rosengren, A; Skoglund, K
Abstract: Background: Congenital aortic valve stenosis (CAVS) accounts for almost 5% of congenital heart defects. Increased survival has been reported in patients with complex congenital heart defects over the last decade. However, data on the long-term outcomes of simple defects such as in isolated CAVS, are still limited. Purpose: The present study aimed to investigate the risk of mortality in patients with isolated CAVS over the last half century in Sweden. Methods: We used data from the Swedish National Patient and Cause of Death Register to identify patients with isolated CAVS born between 1970 and 2017. Each CAVS was matched with 10 controls without congenital heart disease from the Total Population Register, according to sex and birth year. The maximal follow-up time was from birth up to 47.5 years of age. We estimated mortality rates for cases and controls, and the 95% confidence interval (CI) of their ratio. Kaplan-Meier curves were used to estimate the survival for cases and controls under the follow-up. Results: A total of 1, 258 patients with isolated CAVS and 12, 550 matched controls were included in the study. The median follow-up was 24.5 years (interquartile range (IQR):18.0) for cases and 25.5 years (IQR: 17.6) for controls respectively. The overall risk of mortality was more than three times higher for patients with isolated CAVS, compared with matched controls, hazard ratio (HR) 3.1 (95%, CI 2.1–4.5). Survival at 47.5 years of age was 94.1% for cases and 97.3% for controls. Within the first year of life, the mortality risk in patients with isolated CAVS was more than 19 times higher (95%, CI 8.8–43.6) than controls. By contrast, when diagnosed with isolated CAVS above the age of 10 years, the risk of mortality was 2.1 times higher (95%, CI 1.1–3.5) compared to controls. Conclusions: The mortality in patients with isolated CAVS was more than three times higher compared with matched controls. The highest mortality was found in patients with a diagnosis of isolated CAVS diagnosed within the first year after birth, verifying the critical form of the disease. Furthermore, patients diagnosed with isolated CAVS later in life (hence clinically assumed as a mild form of valvulopathy) have a mortality risk twice as high as controls, highlighting the need for follow-up and lifetime management, even in the mild forms of valvulopathies. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Swedish state under an agreement between the Swedish Government and county Councils (ALF)